Essays on migration and tourism in Georgia - Murvanidze, Elene, author; Pena, Anita Alves, advisor; Miller, Ray, committee member; Weiler, Stephan, committee member; Cavdar, Gamze, committee member (Colorado State University. Libraries, 2024)
In the context of the Georgian economy, migration, tourism, and agriculture are fundamental sectors, each significantly influencing the country's socio-economic structure. Migration, driven by economic opportunities and geopolitical factors, impacts labor markets, remittance flows, and cultural diversity. Although emigration has historically led to challenges such as brain drain, remittances from Georgian migrants support household incomes and contribute to GDP. Tourism leverages Georgia's cultural heritage, scenic landscapes, and urban attractions to draw international visitors, creating jobs and generating foreign exchange. Agriculture, with its deep historical and geographical roots, remains crucial for food security, export earnings, and rural livelihoods, benefiting from the diverse crops grown in Georgia's fertile soils. As Georgia progresses economically, understanding and leveraging the interactions between migration, tourism, and agriculture is essential. This requires thorough examination and expansion of existing research to gain deeper insights into their socio-economic impacts. Only through such detailed analysis can policymakers develop strategic policies and make informed decisions. This dissertation aims to represent one small step towards this goal. Since 1990, over one million individuals, comprising about 25% of the country's population, have emigrated from Georgia due to political instability, security concerns, and socioeconomic challenges. Among the 25 East European and former Soviet countries, only Albania and Kazakhstan have experienced a greater proportion of population loss through emigration. Women constitute over half of all migrants, 39% of Georgian children reside in households with at least one migrant family member, and 19% of children live in households that receive remittances. Public discussions surrounding migration have subtly evolved: the stigma attached to independent female migrants for "abandoning" their families has gradually given way to an acknowledgment of their role in ensuring household survival. The first chapter of this dissertation examines the relationship between remittances and the education outcomes of children left behind. We use the 2012 household survey collected by Maastricht University and the International Centre for Social Research and Policy Analysis and measure the impacts on education outcomes of children between 11 and 18 years old. We estimate results for being a high academic performer (probit model), and average academic scores (OLS model). Our findings show that remittances do not impact children's school performance. When we control for migrant characteristics, we find that the migration of a female household member negatively impacts the child's school performance. To further investigate the impact of migrant gender on school performance, we analyze the child's current caregiver arrangements. The results show that a child's education outcomes are negatively impacted when mother is abroad and father is a caregiver. The impact is larger for girls than for boys. We do not find statistically significant evidence of adverse effects when fathers migrate and mothers are caregivers, or when both parents migrate and grandparents are caregivers. Remittances do not have a statistically significant impact in any of our specifications (in rural or urban settings, for daughters or sons). The dissolution of the Soviet Union drastically transformed the Georgian economy. High rates of unemployment and poverty, prompted the government to reconsider its economic strategies. Recognizing the need to diversify the economy, particular emphasis was placed on boosting the tourism sector. From 2009 to 2016, Georgia had one of the fastest-growing tourism sectors in the world. The number of international visitors quadrupled, and the tourism revenue as a share of GDP increased eight-fold. Despite the pivotal role played by tourism development in Georgia's economic landscape and policy formulation, its effects have not been extensively studied. There is no research indicating that the development of tourism in Georgia leads to sustainable economic growth. The second chapter investigates the impact of tourism development on economic growth. We utilize the autoregressive distributed lag bounds testing (ARDLBT) model, examining both annual data spanning from 1997 to 2019 and quarterly data from 2011 to 2019. The annual data results for the trivariate model (real GDP, tourism, real effective exchange rate) confirm Aliyev and Ahmadova's (2020) findings. Cointegration tests indicate the relationship between tourism and economic growth, a 1% increase in tourism arrivals is associated with a 0.14% decrease in real GDP. However, once we add agriculture (AGR) and foreign direct investments (FDI) as additional controls we do not find the long-run relationship between tourism and real GDP to be statistically significant. These conclusions are consistent across various model specifications and are further supported by our analysis of quarterly data. In terms of other tourism impacts, we find tourism to have a positive impact on the real effective exchange rate (REER), a 1% increase in tourism development is associated with a 0.08-0.19% increase in REER in the long-run. Additionally, tourism demonstrates short-term correlations with agriculture (AGR) and foreign direct investment (FDI), with a 1% increase in tourism development corresponding to increases of 0.11-0.49% in AGR and 1.07-1.46% in FDI. The third chapter evaluates the effects of protected areas on land use and income distribution, focusing on changes in tourism and agricultural production in a theoretical framework. Our findings show that conservation policy has economic and environmental consequences even when it does not directly intersect the agricultural frontier. The establishment or expansion of the protected area tends to attract more visitors. The growth of tourism and agricultural sectors will raise nominal wages and agricultural prices. The extent of these changes will determine whether inequality increases or decreases.